Letter - Willis, Robert
034-0038-001 Established 1860 Affiliated membership over 300,000 TELEPHONES EUSTON 3644 | ST ALBANS 1567 LONDON TRADES COUNCIL Secretary: ROBERT WILLIS To whom all communications should be addressed Cheques should be made payable to: "The London Trades Council" 5, Endsleigh Gdns. London, W.C.1 28, Alma Road St. Albans, Herts. Mr. V. Feather, Organisation Department, Trades Union Congress, Transport House, Smith Square, London, S. W. 1. Have word with Carthy Dear Mr. Feather, I have had a communication from the International Brigade Association in which they are asking for the assistance of the London Trades Council in a campaign they are organising with regard to certain International Brigaders still interned in France. Would you be good enough to let me know whether this organisation is proscribed by Congress? Yours sincerely, Robert Willis Secretary 292/946/34/38